1957
DOI: 10.1161/01.res.5.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Fibrillation and Ion Transport

Abstract: Ventricular fibrillation has been studied by driving the ventricles of the isolated rabbit heart electrically and observing whether fibrillation persisted after stimulation was stopped. The hearts were perfused by solutions of different ionic composition and the proportion of hearts in which persistent fibrillation was seen was determined for each solution. The proportion was controlled from 0 to 100 per cent according to the amount of K + , hearts fibrillating spontaneously in .25 N K + . A similar study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

1957
1957
1968
1968

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 7 publications
1
23
1
Order By: Relevance
“…This method of arresting fibrillation was described by Dirken, Gevers, Heemstra and Huizing (1955). Effects of Chloroquine, Mepacrine and Pyrimethamine.- Armitage (1957) has observed that chloroquine, mepacrine and pyrimethamine have a quinidine-like action on the electrically-driven rabbit atria (Dawes, 1946). It therefore seemed likely that these substances would be effective in abolishing fibrillation, and their action was tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of arresting fibrillation was described by Dirken, Gevers, Heemstra and Huizing (1955). Effects of Chloroquine, Mepacrine and Pyrimethamine.- Armitage (1957) has observed that chloroquine, mepacrine and pyrimethamine have a quinidine-like action on the electrically-driven rabbit atria (Dawes, 1946). It therefore seemed likely that these substances would be effective in abolishing fibrillation, and their action was tested.…”
Section: Resultsmentioning
confidence: 99%
“…Armitage (1957) has shown that, when the isolated atria are exposed to the action of these substances, the contractions diminish in amplitude and frequency until they stop. They begin again when the external potassium concentration is lowered to one-half or one-quarter.…”
Section: Resultsmentioning
confidence: 99%
“…Use was then made of the observation (Armitage, Burn, and Gunning, 1957) that, when the potassium concentration was lowered, the proportion of hearts fibrillating was increased. The following experiment is an example.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholine shortens the atrial action potential (Hoffman and Suckling, 1953) and facilitates atrial fibrillation in the dog (Burn, Vaughan Williams, and Walker, 1955). Acetylcholine has practically no effect on the ventricular action potential (Hoffman and Suckling, 1953) and has no effect on ventricular fibrillation (Armitage, Burn, and Gunning, 1957). Adrenaline lengthens the atrial action potential in the rat (Webb and Hollander, 1956), and prevents acetylcholine from causing atrial fibrillation (Burn, Gunning, and Walker, 1957).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation